Does Extraction or Retention of the Wisdom Tooth at the Time of Surgery for Open Reduction and Internal Fixation of the Mandible Alter the Patient Outcome?. Issue 4 (December 2015) - Hammond, Douglas; Parmar, Sat; Whitty, Justin; Pigadas, Nick
Whether to extract or retain wisdom teeth present in a fracture line is a controversial topic. This study reviewed the records of all patients who had mandibular wisdom teeth at the time of the injury, and had an open reduction and internal fixation procedure between January 2009 and January 2012. The cohort of patients who concomitantly had their wisdom tooth extracted at the time of fixation had a greater complication rate (24.3%) compared with patients who did not (14.9%). This suggests that if third molars in the line of a fracture have caries, are fractured, show signs of pericoronitis, are periodontally involved, or are interfering with the occlusion are extracted at the time of fixation, this will increase the incidence of complications.